2001
DOI: 10.1080/01650250042000203
|View full text |Cite
|
Sign up to set email alerts
|

Improving young children’s free narratives about an observed event: The effects of nonspecific verbal prompts

Abstract: The aim of the present study was to evaluate the efficacy of two nonspecific verbal prompts in interviewing preschool children and second graders. Forty kindergartners (M age = 71.6 months) and 46 second graders (M age = 97.6 months) watched a 7 minute video about a gang of adolescent boys stealing money from another youth. Three weeks later they were interviewed about the content of the film under two experimental conditions. Both groups were first asked to report everything that they could remember about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…However, all children benefited from the verbal prompts in association with the cue cards. Two recent studies have demonstrated increased recall from children verbally prompted to recall everything they heard, and everything they saw and the present findings confirm the value of these general open-ended prompts (Elischberger and Roebers, 2001;Poole and Lindsay, 1995).…”
Section: Discussionsupporting
confidence: 88%
“…However, all children benefited from the verbal prompts in association with the cue cards. Two recent studies have demonstrated increased recall from children verbally prompted to recall everything they heard, and everything they saw and the present findings confirm the value of these general open-ended prompts (Elischberger and Roebers, 2001;Poole and Lindsay, 1995).…”
Section: Discussionsupporting
confidence: 88%
“…Elischiberger and Roebers (2001) found modest correlations between verbal IQ and quantitative measures of eyewitness recall in 7-year olds, although correlations for 5-year olds did not reach significance. Geddie, Fradin, and Beer (2000) found positive relationships between IQ and both recall and suggestibility in preschoolers, although other variables such as race, age and metamemory scores were more powerful independent predictors.…”
Section: Intelligencementioning
confidence: 67%
“…Interestingly, several researchers have shown that the gains associated with the NET can be obtained simply by providing verbal prompts for the same categories of information cued using the NET cue cards, without training in how to talk about the past (Bowen & Howie, 2002;Brown & Pipe, 2003a, 2003bElischberger & Roebers, 2001). In other words, simply asking children to report what they saw and heard (Poole & Lindsay, 1995) or to talk about different categories of information (Quas et al, 2000) can produce increases in the amounts of information reported.…”
Section: Probing Memorymentioning
confidence: 99%